Transcriptome Alterations Following Loss of PIP5K1α Function in Prostate Cancer Cells - Morris, Ryan (2023)
The human genome encodes three membrane-targeted phosphatidylinositol-4-phosphate 5-kinases (PIP5K1α, PIP5K1β and PIP5K1γ) that generate the signalling molecule phosphatidylinositol 4,5-bisphosphate [PI(4,5)P2]. These lipid kinases target the 5th position of the inositol ring structure located on phosphatidylinositol 4-phosphate [PI(4)P]. PI(4,5)P2 acts as a key second messenger in cells, involved in regulation of many cellular processes, a major aspect of which is through the activation of PI3K/AKT and PKC signalling pathways. Dysregulation of these pathways through gene alterations is commonly associated with oncogenesis, resulting in sustained cell proliferation, aberrant cell migration, evasion of apoptosis and increased angiogenic potential. In the context of prostate cancer, inactivation of the tumour suppressor gene PTEN occurs in ~50% of advanced malignancies, with this a main driver in oncogenesis. More recently, it has been identified that PIP5K1A gene amplifications are found in ~10% of advanced prostate cancers, however the role that this kinase exerts in prostate tumorigenesis has been less studied.